Complete genome analysis of Lactobacillus fermentum YLF016 and its probiotic characteristics. (January 2022) - Zhang, Lihong; Ma, Hongcai; Kulyar, Muhammad Fakhar-e-Alam; Pan, Huachun; Li, Kewei; Li, Aoyun; Mo, Quan; Wang, Yaping; Dong, Hailong; Bao, Yuhua; Li, Jiakui
Abstract: Lactobacillus fermentum ( L. fermentum ) YLF016 is a well-characterized probiotic with several favorable characteristics. This study aimed to analyze the probiotic characteristics of L. fermentum and uncover the genes implicated in its potential probiotic ability on the base of its genomics features. The complete genome of L. fermentum YLF016 was found to have a circular chromosome of 2, 094, 354 bp, and 51.46% G + C content without any plasmid. Its chromosome contained 2, 130 predicted protein-encoding genes, 58 tRNA, and 15 rRNA-encoding genes. Also, it was found to have many other probiotic properties, such as a high survival rate in the gastrointestinal tract with strong adherence to intestinal cells, antibacterial activity against pathogens, and antioxidant activity. Moreover, the genome sequence analysis demonstrated specific genes coding for carbon metabolism pathway, genetic adaption, stress resistance, and adhesive ability. Further analysis revealed its non-hemolytic activity and its non-functional ability of virulence factors. In conclusion, L. fermentum YLF016 possesses many valuable probiotic properties that refer to its potential probiotic ability. Highlights: Lactobacillus fermentum is a well-characterized probiotic with several favorable characteristics. It uncovers potential probiotic ability on the base of its genomics features. Genome sequence revealed specific genes for carbon metabolism, genetic adaption, stress resistance, and adhesive ability. It has high survival rate in the gastrointestinal tract with strong adherence to intestinal cells. It possesses many valuable probiotic properties that refer to its potential probiotic ability.